2015
DOI: 10.1002/chem.201502170
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐Doped Graphene Oxide Layer as a Highly Efficient Flame Retardant

Abstract: A simple and easy process has been developed to efficiently dope phosphorus into a graphene oxide surface. Phosphorus-doped graphene oxide (PGO) is prepared by the treatment of polyphosphoric acid with phosphoric acid followed by addition of a graphene oxide solution while maintaining a pH of around 5 by addition of NaOH solution. The resulting materials are characterized by X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), Raman spectroscopy, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…The flame retardant graphene-based nanocomposite flame retardants can be classified into three categories: inorganic acids molecules graphene-nanocomposite flame retardants, P-, Si-or N-containing molecules graphene-nanocomposite flame retardants and conventional-organic flame retardant molecules graphene-nanocomposite flame retardants. Phosphoric acid [71][72][73] and phosphomolybdic acid [74] are examples of the substances that can be used to make inorganic acid graphene-nanocomposite flame retardants. They attach to graphene and disrupt the interfaces between graphene sheets, improving the dispersion of graphene in polymer matrices.…”
Section: Molecules-modified Graphene Composite Flame Retardantsmentioning
confidence: 99%
“…The flame retardant graphene-based nanocomposite flame retardants can be classified into three categories: inorganic acids molecules graphene-nanocomposite flame retardants, P-, Si-or N-containing molecules graphene-nanocomposite flame retardants and conventional-organic flame retardant molecules graphene-nanocomposite flame retardants. Phosphoric acid [71][72][73] and phosphomolybdic acid [74] are examples of the substances that can be used to make inorganic acid graphene-nanocomposite flame retardants. They attach to graphene and disrupt the interfaces between graphene sheets, improving the dispersion of graphene in polymer matrices.…”
Section: Molecules-modified Graphene Composite Flame Retardantsmentioning
confidence: 99%
“…The interlayer distances in GO, GO‐PVA and PVA were confirmed by using powder X‐ray diffraction method. As literature suggested that the 2θ peak for graphite powder is at 26.710 which corresponds to the interlayer distance of 3.34 Å in graphite . The as‐prepared GO showed a 2θ peak at 11.520, which confirms that the graphite was fully oxidized into GO with interlayer distance of 7.7 Å.…”
Section: Resultsmentioning
confidence: 56%
“…Other peaks at 1410 cm −1 and 1049 cm −1 were for C−H bending and C−O stretching. All the observed peaks indicates that the graphite was considerably oxidized and successfully converted into the GO . New peaks were appeared at 2933 cm −1 for C−H stretching, 3334 cm −1 for O−H stretching, 1718 cm −1 for C=O stretching and1048 cm −1 indicating C−O stretching bonds after the functionalization with PVA .…”
Section: Resultsmentioning
confidence: 94%
“…The C1s spectra of all samples are shown in Figure A, and the specific values are listed in Table . As can be seen clearly, there are 3 peaks located at 284.7, 285.8, and 287.5 eV, representing the structure of aliphatic and aromatic carbon atoms (C─C and C ─H) and carbon atoms belonging to either the ether linkage or hydroxyl (C─O) and the carbonyl carbon atoms (C═O), respectively . As usual, the C ox and C a can be used to identify the amounts of oxidation (C─O and C═O) and nonoxidation (C─C and C─H) carbon atoms, respectively.…”
Section: Resultsmentioning
confidence: 99%